Relationship between dental occlusion and brain activity: A narrative review - Sebastian Silva Ulloa; Ana Lucía Cordero Ordóñez; Vinicio Egidio Barzallo Sardi (Saudi Dental Journal)
Objectives: Occlusal function stimulates different areas of the cerebral cortex. The purpose of this narrative review was to identify the relationship between occlusion and brain activity so as to provide theoretical support to enable future studies on the subject. Study selection, data, and sources: Relevant case-control studies, clinical trials, and systematic reviews available in English were retrieved from the following databases: MEDLINE, PubMed, ScienceDirect, Wiley Online Library, and Biblioteca Virtual en Salud (BVS). Of the 53 articles obtained, 12 were included. Conclusion: The sensorimotor cortex is affected by changes in occlusion. It is speculated that occlusion could play an important role in the development of diseases, from anxiety and stress to Alzheimer’s disease and senile dementia. Further investigations into the interactions between occlusion and brain function are needed to elucidate the parts of the brain that are affected when occlusion is disturbed and to determine whether brain function is altered. Clinical significance: Dentists must consider that alterations in the occlusal pattern during mastication can lead to changes in the activation of different brain regions related to memory, learning, anticipatory pain, and anxiety. This suggests that mastication maintains the integrity of certain brain areas and that it may be a key factor in the onset of neurodegenerative diseases.